High‐Throughput Contact Flow Lithography. Issue 10 (24th June 2015) - Le Goff, Gaelle C.; Lee, Jiseok; Gupta, Ankur; Hill, William Adam; Doyle, Patrick S.
<x xml:space="preserve">Abstract</x> High‐throughput fabrication of graphically encoded hydrogel microparticles is achieved by combining flow contact lithography in a multichannel microfluidic device and a high capacity 25 mm LED UV source. Production rates of chemically homogeneous particles are improved by two orders of magnitude. Additionally, the custom‐built contact lithography instrument provides an affordable solution for patterning complex microstructures on surfaces.